Efficacy of Bottle Gourd Seeds’ Extracts in Chemical Hazard Reduction Secreted as Toxigenic Fungi Metabolites - Adel G. Abdel-Razek; Ahmed N. Badr; Salman S. Alharthi; Khaled A. Selim (Toxins, 2021)
Bottle gourd seeds are surrounded by innumerable bioactive components of phytochemicals. This work aimed to evaluate the effectiveness of bottle gourd extracts as antimicrobial and an-ti-mycotoxigenic against toxigenic fungi and mycotoxins. Polar and nonpolar extracts were made from the seeds. The polar eco-friendly extract was prepared by an ultrasonication-assisted technique utilizing aqueous isopropanol (80%), whereas the non-polar extract was obtained using petroleum ether (40–60). The antioxidant efficacy, total phenolic content, and flavonoid content of the extracts were all measured. The fatty acid profile was measured using GC equipment, and the influence on toxigenic fungus and mycotoxin release was also investigated. The antioxidant efficacy of the polar extract is reflected. The total phenolic values of the oil and polar extract were 15.5 and 267 mg of GAE/g, respectively. The total flavonoid content of the oil was 2.95 mg catechol/g, whereas the isopropyl extract of seeds contained 14.86 mg catechol/g. The polar extract inhibited the DPPH more effectively than oil. When compared to other seed oils, the fatty acid composition differed. The pathogens were distinguished by the MIC and MFC for the polar extract. Three sterols were found in the oil, with a high concentration of B-sitosterols. The oil’s valuable -carotene content and tocopherol content were recorded. When compared to traditional antibiotics, the polar extract has shown promising antimicrobial activity against infections and toxigenic fungi. Bottle gourd extracts, as a non-traditional bioactive source, are viewed as a potentially promising alternative that might contribute to increased food safety, shelf-life, and security.